“La banda de pueblo como elemento de construcción social y su incidencia en los habitantes de la parroquia Calpi, comprendidos entre los 50 a 75 años en el período de enero a diciembre del 2015 - Vaca Cárdenas, Antoni Neptalí (2017)
Ecuador is one of the countries of America, where music plays an important role in its history. Thus, the present research determines the incidence of the village band as an element of social construction of the habitants of the Santiago de Calpi parish. The village bands represent one of the most symbolic traditions of popular culture, they have a very close relationship with the community and its development, they are a link that expresses deep feelings; they are considered like the musical inheritance of the ancestral towns. For these characteristics, structuralist and cultural anthropological theories were applied in the research. Within the methodological process the main factors that determine that the band of people is considered an element of social construction, with the application of the scientific, inductive, descriptive and analytical methods. The research design was field-based and non-experimental, becasuse the variables were not manipulated, data collection techniques were also detailed, in this case surveys and interviews allowed obtaining specific information from the population sample and experts in the field. The results allowed determine that the musical tradition of the village bands is kept alive and transmitted from generation to generation in the parish of Santiago de Calpi, it is considered as an element of social construction of their identity. Calpi is identified as a land of musicians. In ancient times the musicians played the instruments in the ear, acquired the musical knowledge with a particular teacher called MAESTRO MAYOR. Later with the creation of musical educational institutions, the young began to professionalize themselves. Despite this, the recognition and popularity of the village bands has declined, for this reason it is necessary to disseminate, keep and promote its importance and social-cultural value with the use of audio-visual products as the result of this work.